PISA and Sustainable Development Goals: Comparing Science Curricula in Secondary Schools in Indonesia, Singapore, Australia, and Canada in the Content Aspect Based on the PISA 2025 Framework - Hakim, Abdul; Safrudiannur; Zahra, Ince Raudhiah; Mannan, Muhammad Nur; Sundari, P. D.; Norsaputra, Ary (Universitas Negeri Semarang, 2025)
Continuous curriculum updates are crucial for enhancing the quality of education, improving citizens' global competitiveness, and supporting Sustainable Development Goal (SDG) 4, particularly the goal of achieving quality education for all. International studies, such as PISA, have attracted many researchers interested in comparative curricula across PISA-participating countries. Unlike previous studies, this research compares the science curricula of Indonesia, Singapore, Australia, and Canada based on the science content tested in the PISA 2015, PISA 2021, and PISA 2025 frameworks. The method used in this study is content analysis. We searched for documents from the four countries on their respective Ministries of Education websites. After obtaining the documents, two researchers independently conducted the coding analysis. After that, the researchers validated the content analysis through inter-rater agreement. The results show that the science curricula of Indonesia, Singapore, Australia, and Canada do not specifically cover all content in the PISA 2015, PISA 2021, and PISA 2025 frameworks. Specifically, Singapore's curriculum documents do not cover Earth and Space System content, while Labrador, Alberta, and British Columbia cover all themes. The Indonesian science curriculum encompasses all themes assessed in PISA questions and the PISA 2025 framework, although it does not yet cover all topics. However, it remains challenging to pinpoint the reasons for the differences in PISA results among the four countries in this comparative study.